La fiscalita’ delle P.M.I. tra distretti produttivi e reti di impresa - Tassani, Thomas (Piccola Impresa / Small Business, 2007)
The article discusses the Italian tax regime for small and medium-sized enterprises, in particular in regard to income tax. The first topic which is examined is the EU policy for small and medium enterprises (SMEs), especially the documents held by the institutions of the European Union to promote the implementation of a favourable SME tax regime. Then the relevant Italian tax law for SMEs is discussed. Given the lack of Italian tax regimes that favour the development of small and medium-sized enterprises, the article focuses on specific tax provisions for industry districts; these provisions were included in the Italian Financial Act of 2007, but they were never implemented. The analysis of both the positive and negative aspects of the industry districts system is the basis for evaluating proposals by tax academics and political figures for tax provisions for firm networks. Firm networks could represent a permanent factor that will contribute to economic growth, in particular for small and medium-sized enterprises, provided that this regime is defined coherently, and respects both national constitutional principles and the principles of the European Union.